Enhanced thermal-hydraulic performance in tubes of reciprocating scraped surface heat exchangers. (5th February 2023) - Solano, J.P.; Martínez, D.S.; Vicente, P.G.; Viedma, A.
Abstract: An experimental study of pressure drop and heat transfer in tubes of reciprocating scraped surface heat exchangers is presented. Inside the tube, a concentric rod which mounts an array of equally-spaced semi-circular blades is fitted. The reciprocating motion of the rod induces the continuous scraping of the inner tube wall, enhancing heat transfer through the removal of the thermal boundary layer, the promotion of mixing of the bulk flow and the mitigation of fouling. Using propylene-glycol as working fluid, friction factor results in isothermal conditions are obtained for 15 < Re h < 1500 and velocity ratios 0 < ω < 2 . Early transition to turbulence for Re h < 150 is detected. Pressure drop augmentations of the order of 20, with respect to the smooth tube, are found in laminar regime for ω = 2 . In the turbulent flow regime, this pressure drop increase rises up to 400 times. In laminar regime, results for ω = 0 . 1 lead to heat transfer augmentation of 30 % compared with the smooth tube. When increasing from ω = 0 . 1 to ω = 1, the Nusselt number is doubled. However, when increasing from ω = 0 . 1 to ω = 2 the Nusselt number is only increased by 2.8 times. The beneficial influence of higher scraping amplitudes on heat transfer have been demonstrated, as well as their negligible impact on the friction characteristics. Graphical abstract: Highlights: Experimental analysis of reciprocating scraped surface heat exchanger tube is conducted. Fanning friction factor in motionless and scraping conditions is defined. Early transition to turbulence for Reh ¡150 is detected in all operating conditions. Nusselt number increases up to 2.8 times with higher scraping velocities.